A result concerning nilpotent values with generalized skew derivations on Lie ideals. Issue 12 (2nd December 2018) - Sharma, R. K.; Dhara, B.; Filippis, V. De; Garg, C.
ABSTRACT: Let n ≥1 be a fixed integer, R a prime ring with its right Martindale quotient ring Q, C the extended centroid, and L a non-central Lie ideal of R . If F is a generalized skew derivation of R such that ( F ( x ) F ( y )− yx ) n  = 0 for all x, y ∈ L, then char ( R ) = 2 and R ⊆ M 2 ( C ), the ring of 2×2 matrices over C .